The co-Mingling Between the Post Modern Architecture and Sculptural Design to Create Contemporary Design for Ladies - sarah mohamed ali gomaa gomaa (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2022)
The worlds of architecture and fashion share design concepts such as art and technology in aesthetic terms, form, materials, and architecture. The design was submitted for architecture and sculptural design, the parallel relationship between Fields ready for constant changes in taste and styles.Architecture and fashion provide shelter for humans on different scales (architecture on a larger scale).Architecture protects them from natural phenomena and creates a safe and private environment for them. Fashion, on the other hand, provides shelter as a skin.Architecture as a “third skin” surrounds the human body with the space around it, and people move and spend time in it, while the sculptural design gives a figurative composition.Dress Sculpture explores the impact of non-traditional materials on three-dimensional art practice, as artists have used cloth, fur, rope, rubber, paper, leather, vinyl, plastic, and other new materials to create static rather than permanent shapes. The choice of these materials emphasize natural forces, such as gravity and heat, and in many cases have metaphysical or metaphysical effects